Ensuring quality inclusive and equitable education by increasing emotional intelligence through positive attitudes in students' learning from mistakes - Dogaru, Mariana; Pisică, Olivia; Vaşcu, Janina-Elena (Frontiers in Education, 2025)
Our study examines how teachers' affirmative responses to student errors can cultivate emotional intelligence and advance inclusive, equitable education in accordance with Sustainable Development Goal 4 (SDG4), while addressing the issue of error-related anxiety in high-stakes, performance-oriented educational systems that frequently diminish student resilience and engagement. We employed a mixed-methods design to survey 236 students (grades 5–8) and 46 teachers from urban and rural secondary schools in Romania, utilizing customized questionnaires (Cronbach's α = 0.82 for students, 0.78 for teachers) that integrated Likert-scale items and open-ended questions. We used SPSS 20 to look at the quantitative data (descriptive statistics, Pearson correlations, ANOVA) and thematic coding to look at the qualitative data (Cohen's Kappa = 0.84 for inter-code reliability). The results showed that most students (56%) see mistakes as obstacles at first, but positive feedback from teachers can help students stay strong and motivated (for example, 48% said they were motivated by phrases like “Next time will be better”). Teachers' methods were different; 80% encouraged students to learn from their mistakes, while 15% used criticism, which had a big effect on how students felt (for example, 65% said they were anxious after getting harsh feedback). Hypotheses H1 and H2 were validated, affirming the constructive function of mistakes and the emotional influence of error management, whereas H3 was not supported, indicating no significant correlation between knowledge accessibility/error identification and teacher job satisfaction (p>0.05). Therefore, study suggests that teachers should get specific training in emotional intelligence and how to make classrooms more welcoming for mistakes. This will help create supportive environments and give teachers practical ideas for how to teach fairly in settings with different resources.